2016
DOI: 10.1007/s10562-016-1919-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Pyrolysis Temperature on the Material Properties of Cobalt and Nickel Containing Precursor Derived Ceramics and their Catalytic Use for CO2 Methanation and Fischer–Tropsch Synthesis

Abstract: Ni and Co containing precursor derived ceramics (ceramers) were prepared from a polysiloxane based preparation route. All catalysts were characterised by BET, XRD and TEM as well as water and heptane adsorption and tested for CO2-methanation and Fischer-Tropsch synthesis. Different pyrolysis temperature between 400 and 600 °C were used to get catalysts with different surface hydrophilicities. With increasing synthesis temperature less organic groups remain on the surface resulting in a more hydrophilic catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Consequently, the decomposition of the methyl group in MK is shifted to lower temperatures as it was observed in previous TGA measurements. This behavior of polysiloxanes has been reported in literature for nickel as well as for other metals . Studies using similar precursors found comparable BET SSA.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Consequently, the decomposition of the methyl group in MK is shifted to lower temperatures as it was observed in previous TGA measurements. This behavior of polysiloxanes has been reported in literature for nickel as well as for other metals . Studies using similar precursors found comparable BET SSA.…”
Section: Resultssupporting
confidence: 88%
“…Thus, a connection of the Ni ion to the polymeric chain can be assumed as it was reported previously. 11,13,35 This is not true for the sample NiA2TMEDA/600 where the complexing agent TMEDA has no cross-linking active groups. Consequently, binding of the complexed Ni ions to the polymeric chain is not possible.…”
Section: Influencing Factors On Ni Particle Sizementioning
confidence: 97%
“…The organosilane ((3‐Aminopropyl)triethoxysilane) play an influential role as complexing and cross‐linking agent in the synthesis of intermetallic nickel/cobalt silicide particles upon SiOC matrix. The metal ions are chemically attached to the functional groups of the APTES (amino group ‐NH 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[12] The essential modification can be implemented in the sequence of stride during the formation of PDC by utilizing suitable polymer precursor, active fillers, complexing agents and pyrolysis temperature to acquire required morphology and active sites. [12][13][14][15][16] Silicon-oxy-carbide (SiOC) structures synthesized from polysiloxane polymers suitably cross-linked and pyrolysed at elevated temperature are relevant PDC structure with unique two-phase structure such as (i) the amorphous phase where Si is tetrahedrally bonded with oxygen and carbon; (ii) disordered carbon phase holding excellent chemical, thermal and physical properties that can be employed as bifunctional catalyst. [13,[17][18][19][20] The addition of precursor for transition metal particles such as cobalt and nickel at the atomic level is crucial in enhancing the properties such as electrochemical activity and conductivity of the SiOC material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation